PENERPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA (Studi Pada Mata Pelajaran IPS Siswa Kelas IV SD Negeri 11 Merapi Barat Lahat) - Fifien Erfianty (DIADIK, 2020)
Thisstudy aimstoDescribetheapplicationoftheProblemBasedLearning(PBL)learning model,Describetheimprovementof studentlearningincreaseforactivitiesandDescribethe learningachievementsofstudentsatsocialstudiessubjectsin classIVSDNegeri 11Merapi BaratLahat.TheresearchmethodusedwasClassroom ActionResearch(CAR)andquasi- experiments.  The  research  subjects  were  fourth  grade  students  of  semester  two  of  the 2019/2020schoolyearSDNegeri11MerapiBaratLahat.Forquasi-experimentalsamples areclassIVA,classIVBandIVC.Thenumber ofstudentsfor the CARclassis20students, fortheExperimentclassthereare20,andforthecontrol classthereare20students.Data collection  methods  in  this  studyused  assessment  test.  Data  analysis  uses  mean  means, percentageandt-tests.TheresultsofthestudyshowthatTheapplicationoftheProblem BasedLearningmodel canimprovestudentlearningactivities,Canimprovestudentlearning achievementimprovestudentlearningoutcomesinSopsalScience (IPS)subjects